Stress des médecins dans les hôpitaux publics : facteurs de risque et influence sur les compétences professionnelles - Maa Mawo Jeanne Dorothée (African Scientific Journal, 2023)
It is unusual to admit that health care workers, especially medical staff, may also need to be cared for. However, the scientific literature shows us that medical doctors may need support in many ways. Indeed, a better understanding of occupational stress with a view to its effective management and even prevention can contribute to a sustainable improvement in the daily lives of physicians. How does physicians' stress influence their knowledge, skills and attitudes in public hospitals? In order to answer this question, our work, which was granted a Mandate by the Minister of Public Health, consisted in establishing the link between the stress of doctors in public hospitals and their professional skills. More specifically, the aim was to determine the socio-professional distribution of doctors at risk, to gain a better understanding of the psycho-social risk factors associated with this stress and to find out how this stress influences the knowledge, attitudes and abilities of medical practitioners in public hospitals. Based on a hypothetico-deductive approach, a quantitative study was carried out among 81 doctors of various specialities practising in the country, by means of a self-questionnaire filled in online from 11 September 2021 to 18 September 2021. The determinants of physicians' occupational stress were identified using the Karasek and Siegrist questionnaires. The data collection phase was followed by statistical analysis using SPSS version 10.0 for Windows, R and Excel. Correlation tests were also carried out using Bravais-Pearson's linear correlation test and causality tests using Granger's causality test. The Karasek questionnaire revealed that 62.96% of the medical doctors surveyed had exposure to Job Strain stress and 62.96% had exposure to Isostrain stress. The Siegrist questionnaire showed that 71.60% of the medical doctors surveyed were exposed to stress related to Effort/Reward Imbalance and 39.51% were exposed to stress related to Over-investment. And recommendations were made.